Shift : transform motion into progress in business - Lees, Richard (Chief strategy officer); Raj, Azlan (John Wiley & Sons Ltd., 2022)
"Pretty much every business today is trying to deliver the best and most inclusive customer experience for their customers because it is seen as being a source of sustainable competitive advantage for the businesses that can achieve it, and Merkle is very much at the core of making this happen for its clients. BUT, every business approaches this in a different way, and very few achieve the optimum results from their investments. They do a lot of things, ACTION, but they don't maximise the effect of that action and so fail to turn it into PROGRESS. The real reason that businesses want to deliver an excellent customer experience is to differentiate their business from the competition, and drive long term customer engagement. When you measure your actions through the eyes of the technology and other investments the business makes, all you can measure are small outcomes. When you measure it through the eyes of the customer, and the measures that matter to customers are improving, that is real Progress towards these business goals. Action will have translated into Progress. At its core, The Book of Progress is about EVERYTHING we do at Merkle. This book will show you how to deliver an excellent customer experience that guarantees PROGRESS as a result"--